1982
DOI: 10.1029/jc087ic07p04863
|View full text |Cite
|
Sign up to set email alerts
|

The free radical chemistry of cloud droplets and its impact upon the composition of rain

Abstract: Calculations are presented that simulate the free radical chemistries of the gas phase and aqueous phase within a warm cloud during midday. It is demonstrated that in the presence of midday solar fluxes the heterogeneous scavenging of OH and HO2 from the gas phase by cloud droplets can represent a major source of free radicals to cloud water, provided the accommodation or sticking coefficient for these species impinging upon water droplets is ≥10−4. The aqueous‐phase HO2 radicals are found to be converted to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
149
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(154 citation statements)
references
References 63 publications
4
149
1
Order By: Relevance
“…Model studies have shown that cloud droplet losses of OH and HO2 could have important impacts on tropospheric chemistry [Chameides and Davis, 1982;Lelieveld and Crutzen, 1991;Jacob, 1986]. When cloud chemistry is included in these models, gas phase [OH] and [HO2] are reduced by up to 60% and 95%, respectively, compared with gas phase chemistry alone, depending on the pH and chemical composition of the cloud droplets.…”
Section: (R1) 0 3 + Hv --> O(1d) + 0 2 (R2) O(•d) + H20 --> 2oh (R3) mentioning
confidence: 99%
“…Model studies have shown that cloud droplet losses of OH and HO2 could have important impacts on tropospheric chemistry [Chameides and Davis, 1982;Lelieveld and Crutzen, 1991;Jacob, 1986]. When cloud chemistry is included in these models, gas phase [OH] and [HO2] are reduced by up to 60% and 95%, respectively, compared with gas phase chemistry alone, depending on the pH and chemical composition of the cloud droplets.…”
Section: (R1) 0 3 + Hv --> O(1d) + 0 2 (R2) O(•d) + H20 --> 2oh (R3) mentioning
confidence: 99%
“…Both N0 3 and N 2 o 5 possibly could be scavenged by surface reactions with aerosols (Chameides and Davis, 1982). Though the rates of these reactions are unknown, an upper bound can be found from kinetic theory.…”
Section: Aerosol-radical Interactionsmentioning
confidence: 99%
“…Assuming an N0 2 concentration of 0.100 ppm (Tuazon et al, 1981) and an OR radical level of 2x10-7 ppm (Chameides and Davis, 1982), daytime nitric acid production is about 3x10-4 ppm min-1 , less than the production of HN0 3 by reaction 46 after sunset at locations where the NO concentration is negligible (e.g. above the surface layer affected by fresh NO emissions).…”
Section: Nitric Acid Production At Nightmentioning
confidence: 99%
“…The rate constants of OH with dihydrated glyoxal is as large as 1.05×10 9 M −1 s −1 (Buxton et al, 1997) and the corresponding value for monohydrated methylglyoxal is reported to be 1.1 × 10 9 M −1 s −1 (Ervens et al, 2003b) and 0.53 × 10 9 M −1 s −1 (Monod et al, 2005). As for the origin of OH radicals in atmospheric water droplets, gas-phase OH radicals are thought to be the major source (Chameides and Davis, 1982) considering the Henry's law constant of ca. 30 M atm −1 (Sander, 1999).…”
Section: Oh + Toluenementioning
confidence: 98%